2018
DOI: 10.1093/ndt/gfx359
|View full text |Cite
|
Sign up to set email alerts
|

Long-term expression of glomerular genes in diabetic nephropathy

Abstract: The gene profile of BTBR ob/ob type 2 diabetic mice we conducted in this study can help to identify new key players in molecular pathogenesis of diabetic kidney injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 40 publications
1
12
1
Order By: Relevance
“…Among these mechanisms, fatty acid and cellular lipid metabolic dysregulation are of particular interest because lipid abnormalities are increasingly recognized by our group and others as independent risk factors for DKD development. [58][59][60] Importantly, these results are also consistent with recent findings in multiple type 2 diabetic mouse models such as the KK-Ay mouse 61 and the BTBR ob/ob leptin-deficient mouse, 62 further reinforcing our data. Since our findings in this report show association and not causality, direct effects of these increased and decreased gene expression changes will need to be verified experimentally.…”
Section: Discussionsupporting
confidence: 92%
“…Among these mechanisms, fatty acid and cellular lipid metabolic dysregulation are of particular interest because lipid abnormalities are increasingly recognized by our group and others as independent risk factors for DKD development. [58][59][60] Importantly, these results are also consistent with recent findings in multiple type 2 diabetic mouse models such as the KK-Ay mouse 61 and the BTBR ob/ob leptin-deficient mouse, 62 further reinforcing our data. Since our findings in this report show association and not causality, direct effects of these increased and decreased gene expression changes will need to be verified experimentally.…”
Section: Discussionsupporting
confidence: 92%
“…Since we used the renal cortex instead of morphologically dissected glomeruli, this makes direct comparisons difficult. Nonetheless, a number of the reported differentially expressed genes were also found in our data set, e.g., Hdc, Hyal, Hmgcs2, C3, albeit that the total number of DEGs we found was significantly lower than in the study of Chittka et al [31]. Although this is partly due to the use of different arrays (Mouse Whole Transcriptome 1.0 ST array vs.…”
Section: Discussioncontrasting
confidence: 79%
“…Even though renal and serum parameters, as well as some of the histological features in renal tissue, were worse in hCN1 TG mice, the number of DEGs was limited to a subset of 26 genes with a FC-threshold of > 1.5. We cannot, however, exclude that the differences in gene expression profile between diabetic TG and nonTG mice would have been larger if glomeruli were analyzed selectively as previously reported by Chittka et al [31]. Amongst the 26 DEG in diabetic hCN1 TG mice, many have been reported to be pivotal in the pathogenesis of DKD.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Further studies have shown dysregulation of Sema5A and Sema5E in diabetic nephropathy [105]. A large transcriptional dataset on human diabetic glomeruli shows Sema5A and Sema3G are among the top 100 dysregulated transcripts and "semaphorin signaling in neurons" as one of the enriched pathways [128].…”
Section: Semaphorins In Diabetic Nephropathymentioning
confidence: 99%